Law Enforcement, Military Discipline, and the Notion of Military Justice: Building a Case for the Constitutional Rights of Service Personnel in Nigeria - Adegbite, Olusola Babatunde (Faculty of Law, Universitas Negeri Semarang, 2019)
Law enforcement is the pivot on which every society and institution stands and essentially survives on. An institution where enforcement of the law is in abeyance will surely not endure, as whatever goals are set is condemned to smoulder in total indiscipline. Without doubt, no institution would want to set off on that footing. However, where law enforcement takes place in a special institution like the Military, its deployment is bound to raise deep questions regarding the Constitutional rights of the accused persons. Over the years, the Nigerian Military appear to have been caught in this miasma in which the Constitutional rights of its service men has remained trapped in the notion of upholding Military discipline. It is to this end that this paper appraises the question of law enforcement in the Nigerian Military, querying its attitude towards the safeguards of these rights, and accordingly building a case for a new and better regime, in which Constitutional rights of Service personnel are not only guaranteed, but regarded as pre-eminent.